Digital Patient-Reported Monitoring of Functional Recovery After Robot-Assisted Radical Prostatectomy in High-Risk Prostate Cancer Treated With or Without Perioperative Hormonal Therapy - Bogdan Adrian Buhas; Alessandro Uleri; Giorgio Calleris; Guilhem Roubaud; Marine Lesourd; Benjamin Pradère; Christophe Tollon; Damien Pouessel; Bernard Malavaud; Loïc Mourey; Guillaume Ploussard (Diagnostics, 2026)
Background/Objectives: Perioperative androgen-deprivation therapy (ADT) and androgen-receptor pathway inhibitors (ARPIs) are increasingly used in high-risk prostate cancer, yet patient-centred functional-recovery data after radical prostatectomy are scarce and rarely standardized. We assessed whether a smartphone-based digital monitoring pathway could characterize social-continence recovery and capture differences associated with a perioperative hormonal therapy (PHT) strategy after robot-assisted radical prostatectomy with pelvic lymph-node dissection (RARP + LND). Methods: In a two-centre consecutive cohort (n = 98) of men with high-risk, non-metastatic prostate cancer aligned with SUGAR and PROTEUS criteria, we compared upfront surgery (standard of care [SOC], n = 72) with a planned PHT strategy (ADT or ARPI, n = 26); all patients were urinary-continent preoperatively. Clinical data were prospective; patient-reported and patient-experience measures were captured through a routine-care digital platform (Betty Coaching application) delivering an identical prehabilitation/rehabilitation pathway to both groups, with pre- and postoperative pelvic-floor muscle training performed by all patients. The primary endpoint was 6-month social continence (0–1 pad/day), assessed by clinician and patient reports as co-primary sources. Differences are reported as risk differences with 95% confidence intervals (CIs). Results: At 6 weeks, no statistically clear difference was observed (clinician 66.2% vs. 56.5%; risk difference 9.7 percentage points, 95% CI −12 to 32). At 6 months, social continence was lower with PHT (clinician 87.1% vs. 65.0%, difference 22.1 points, 95% CI 2.6 to 44.7; patient 81.3% vs. 58.3%, 22.9 points, 95% CI 2.4 to 43.9), converging by 12 months (96.9% vs. 95.0%). Analgesic-free rates were lower with PHT on postoperative days (POD) 7 and 10. Conclusions: Digital monitoring captured granular recovery trajectories and identified a mid-term social-continence signal associated with PHT, compatible with a transient delay in recovery. These hypothesis-generating findings support embedding standardized digital functional-outcome monitoring in perioperative trials.